Oční víčka se žlutými granulomy a kašel - periokulární xantogranulom dospělých spojený s astmatem. Popis případu a přehled klinických forem juvenilního xantogranulomu a terapie - Adam, Zdenek; Veselý, K; Motyčková, I; Szturz, P; Koukalová, R; Rehák, Z; Stouracová, A; Vaníček, J; Krejčí, M; Pour, L; Zahradová, L; Hájek, R; et al. (Vnitrni lekarstvi, 2012)
Histiocytic diseases caused by proliferation and accumulation of phagocytosing macrophages (foamy macrophages) have many clinical forms. These are classified under "juvenile xanthogranuloma" within the WHO classification of blood disorders. Localized forms with benign course include normolipaemic xanthomatosis, xanthogranuloma and necrobiotic xanthogranuloma. Disseminated forms in children take a form of so called "disseminated juvenile xanthogranuloma" or Erdheim-Chester disease in adults. We describe a case of a patient who, at 53 years of age, first noticed yellow granulomas on her eyelids. The disease progressed gradually and, at 59, affects the eyelids as well as their closest surroundings. According to MR and PET-CT, the disease gradually infiltrated the inside of the orbit, orbital fat as well as extraocular muscles and started to cause exoftalmus of one of the eyes. Propagation of the xanthogranuloma into the orbit and infiltration of extraocular muscles might impair eye function. Over the last year, the patient complained of cough. Pulmonary function evaluation confirmed recent asthma bronchiale. These findings correspond to periocular xanthogranuloma associated with adult-onset asthma. No other abnormities have been shown in this patient. Exoftalmus was observed in 2011 after 6 years of monitoring with very slow progression of eyelid and extraocular infiltration. Therefore, prednisone was initiated in 2011, leading to cessation of exoftalmus. It is not known at present whether this is a permanent improvement with a suppression of histiocytary proliferation or whether this was a temporary improvement due to suppression of inflammatory changes in the xanthogranuloma with no effect on histiocytary proliferation. Progression during therapy with corticosteroids would warrant cytostatic treatment. The discussion section provides an overview of diseases caused by foamy histiocytes with illustrations and an overview of experiences with their treatment.
Keywords: Granuloma; nemoci očních víček; Asthma; bronchiální astma; Humans; lidé středního věku; Female; Erdheim-Chester Disease; lidé; xantomatóza; Xanthomatosis; juvenilní xantogranulom; Erdheimova-Chesterova nemoc; ženské pohlaví; Xanthogranuloma, Juvenile; Middle Aged; granulom; Cough; Eyelid Diseases; kašel